Achieving Wealth Preservation via Islamic Crowdfunding: An Analysis from Maqasidic View - Al-Daihani, Meshari; Sarif, Suhaili; Dirie , Khadar Ahmed; Djafri, Fares; Abdul Muneem (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
Crowdfunding, a modern scheme of raising funds via online platforms, has garnered significant attention in recent years. This study explores crowdfunding through the lens of Islamic jurisprudence, explicitly examining its compatibility with Maqasid al-Shariah (the high objectives of Islamic law). This study utilises a qualitative research approach to explore the harmonious alignment of crowdfunding practices with Islamic principles. The findings illuminate that, despite its modern guise, crowdfunding is profoundly rooted in Islamic traditions, bolstered by diverse interpretations of the Quran and foundational Islamic beliefs. Remarkably, the study affirms that crowdfunding resonates with the essence of Maqasid al-Shariah, especially in its remarkable potential to preserve and enhance wealth (Māl). The implications of this research are crucial for policymakers and Islamic institutions seeking to leverage crowdfunding for economic growth and financial inclusion while adhering to Shariah principles. This study contributes to the growing literature on Islamic finance and fintech, offering a unique perspective on the intersection of faith and technology in financial innovation.